2011
DOI: 10.1242/dev.063867
|View full text |Cite
|
Sign up to set email alerts
|

Rhou maintains the epithelial architecture and facilitates differentiation of the foregut endoderm

Abstract: SUMMARYRhou encodes a Cdc42-related atypical Rho GTPase that influences actin organization in cultured cells. In mouse embryos at earlysomite to early-organogenesis stages, Rhou is expressed in the columnar endoderm epithelium lining the lateral and ventral wall of the anterior intestinal portal. During foregut development, Rhou is downregulated in regions where the epithelium acquires a multilayered morphology heralding the budding of organ primordia. In embryos generated from Rhou knockdown embryonic stem (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 54 publications
6
57
1
Order By: Relevance
“…RhoU-depleted cells had fewer apical microvilli and a reduction in subapical filamentous actin levels. This indicates that RhoU is important for epithelial architecture, 29 consistent with results in vitro with MDCK cells. 25 Apart from the regulation of cell adhesion and cell shape during development, RhoU plays a role in cell migration in developmental models.…”
Section: In Vivo Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…RhoU-depleted cells had fewer apical microvilli and a reduction in subapical filamentous actin levels. This indicates that RhoU is important for epithelial architecture, 29 consistent with results in vitro with MDCK cells. 25 Apart from the regulation of cell adhesion and cell shape during development, RhoU plays a role in cell migration in developmental models.…”
Section: In Vivo Studiessupporting
confidence: 88%
“…[27][28][29] It contributes to the formation of cell-cell junctions between zebrafish cardiomyocytes through a pathway involving the GEF Arhgef7b and PAK1, thereby affecting cardiac morphogenesis. 27 It would be interesting to determine whether PAR6 is involved in RhoU signaling in zebrafish cardiomyocytes, similar to its role in MDCK epithelial cells.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…38 RHOU is hypothesized to maintain the cell architecture through F-actin polarization, and future studies will elucidate the exact mechanisms of this regulation. 39,40 Another study reported that RHOU downregulation diminishes F-actin distribution, reducing the resistance of epithelial cells to compressive force. 41 Changes in RHOU expression may also affect cardiomyocyte resistance to blood pressure overload or other mechanical forces that occur during HF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations indicate that multilayering of the thyroid bud requires Cdc42-mediated apical constriction of progenitors centrally located in the thyroid placode (Loebel et al, 2016). By contrast, knockdown of Rhou, which encodes a Cdc42-related atypical Rho GTPase, paradoxically increases the size of the thyroid bud by a mechanism that appears to involve loss of apical polarity of budding cells (Loebel et al, 2011). Progression of thyroid budding by recruitment from adjacent endoderm might thus be facilitated by directed displacement of progenitors that acquire an unpolarized phenotype as they lose contact with the pharyngeal cavity (Fig.…”
Section: The Proliferation Of Thyroid Progenitors and Follicular Precmentioning
confidence: 99%